A hybrid silicon-PDMS optofluidic platform for sensing applications - Testa, Genni (Optical Society of America, 2014)
A hybrid silicon-poly(dimethysiloxane) (PDMS) optofluidic platform for lab-on-a-chip applications is proposed. A liquid-core waveguide with a self-aligned solid-core waveguide and a microfluidic device are integrated with a multilayer approach, resulting in a three-dimensional device assembly. The optofluidic layer was fabricated with a hybrid silicon-polymer technology, whereas the microfluidic layer was fabricated with a soft lithography technique. The combination of different materials and fabrication processes allows a modular approach, enabling both the benefits from the high optical quality achievable with silicon technology and the low cost of polymer processing. The proposed chip has been tested for fluorescence measurements on Cy5 water solutions, demonstrating the possibility to obtain a limit of detection of 2.5 nM.